Effect of Clinical Interventions on the Incidence of Primary Post-Partum Hemorrhage in Females Undergoing Spontaneous Vaginal Delivery - Iram Khadim, Adnan Yaqoob, Kousar Parveen, Sadia Khan, Muhammad Afzal, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Primary Post-Partum Hemorrhage (PPH) is blood loss 500ml or more commonly occurring during the 3rd and 4th stage of labour, the period is known as delivery of infant with placenta and two hours after delivery. Labor room and delivery room nurses continuously miscalculate blood loss after delivery, which could lead to delay in providing care during Primary Post-Partum Hemorrhage. Objective: To see effect of Clinical Interventions on the Incidence of Primary Post-Partum Hemorrhage in females undergoing spontaneous vaginal delivery (SVD). Methods: Quasi-Experimental study design was used with Pre & Posttest. Incidence of Primary Post-Partum Hemorrhage 196 patients sample was used in this study. Purposive sampling Technique was used in this research. Study setting was all admitted patients in gynae ward of Allied Hospital Faisalabad. The study duration was conducted in September 2021 to May 2022. Maternal age in years 20-50years were including in this study.Femlaes having previous lower segment Caesarean section (LSCS)were excluded from the study. Validated adopted checklist was used to measure incidence rate of Primary Post-Partum Hemorrhage with Cronbach Alpha (0.89). Primary Post-Partum Hemorrhage were labeled as group of “Yes” for right answer & the score was 1 and “No” for wrong answer and score was labeled as “0”. Results: Frequency & Percentages of Demographic variables were checked. During pre-intervention period 39% Incidence rate in females & on the other hand after interventions incidence rate decreases 14% after Spontaneous Vaginal Delivery. This is statistically acceptable. Paired sample t-test was conducted to evaluate the impact of the interventions on females Blood Pressure systolic Pre interventions scores Mean± SD(109.847±12.4303) & Post intervention scores (114.0306±11.30396) with Mean Difference was -4.18367, Paired t test -3.403with P value 0.001.Blood Pressure Diastolic Pre interventions scores Mean± SD(73.2143±8.96575) & Post intervention scores (76.9898±7.06163) with Mean Difference was -3.77551, Paired t test -4.560 with P value 0.000.Pulse Rate in Pre interventions scores Mean± SD(86.3163±6.21346) & Post intervention scores (85.2143±4.63819) with Mean Difference was 1.10204, Paired t test 1.891 with P value 0.060.Temperature in Pre interventions scores Mean± SD(98.1827±.44457) & Post intervention scores (98.1541±.45891) with Mean Difference was .02857, Paired t test .595 with P value 0.553.Respiration in Pre interventions scores Mean± SD(17.3367±1.51196) & Post intervention scores (17.0561±5.98047) with Mean Difference was .28061, Paired t test .625 with P value 0.533.Paired sample t-test was conducted to evaluate the impact of the interventions on females Incidence Rate Pre interventions scores Mean± SD (1.8010 ± .40026) & Post intervention scores (1.9286 ± .25820) with Mean Difference was -1.2755, Paired t test -3.767 with P value 0.00. Conclusion: Clinical Interventions was effective on the Incidence of Primary Post-Partum Hemorrhage in females undergoing spontaneous vaginal delivery. Key Words: Post-Partum hemorrhage, lower segment Caesarean section, Incidence, Females, spontaneous vaginal delivery, Miscalculate.